SOSIALISASI PROGRAM PEMANFAATAN LAHAN PEKARANGAN UNTUK BUDIDAYA SAYURAN SEHAT DI KELOMPOK WANITA TANI DESA CIEREUDEU KECAMATAN PETIR SERANG - Firnia, Dewi (Universitas Sultan Ageng Tirtayasa, 2023)
In general, the people of Cireundeu Village, Petir Subdistrict, Serang, have quite extensiveagricultural land, but its utilization is not optimal. The problem faced by Cireundeu villagers isthat their yard is not maximally utilized. Until now, the yard environment has only been used todry agricultural products, animal feed crops and centuries of little economic value. So far, thecondition of the yard has not helped much to fulfill or support daily needs. In addition, homeyards have not provided added value to cover daily needs, nor have they provided comfort andbeauty. When the yard is organized and empowered, it is expected to add aesthetic value andcontribute to the needs of the community, especially in terms of daily vegetable needs. The generalobjective of this community service activity is to provide an explanation to farmers or farmerwomen group participants about the need for home yard land management for vegetablecultivation and can practice in each of their yard environments. The specific objective of thisactivity is to increase the knowledge and skills of farmers or farm women group participants invegetable cultivation in the home yard environment. This community service activity is carriedout starting from lecture material (Presentation) to gardening practices in the home yard. Fromthis activity it can be concluded that the hobby of growing vegetables in the backyard is very easyfrom a social perspective. In addition, the community has an agricultural background so they arefamiliar with farming. As a result, the backyard environment becomes cleaner and greener, andthe community group can meet the needs of vegetables and medicinal plants around their homes.Keywords: cultivation, optimal, backyard, healthy vegetables